2017
DOI: 10.1007/s00300-017-2164-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α in Antarctic notothenioids contains a polyglutamine and glutamic acid insert that varies in length with phylogeny

Abstract: The long evolution of the Antarctic perciform suborder of Notothenioidei in the icy, oxygen-rich waters of the Southern Ocean may have reduced selective pressure to maintain a hypoxic response. To test this hypothesis, cDNA of the key transcriptional regulator of hypoxic genes, hypoxia-inducible factor-1α (HIF-1α), was sequenced in heart ventricles of the red-blooded notothenioid, Notothenia coriiceps, and the hemoglobinless icefish, Chaenocephalus aceratus. HIF-1α cDNA is 4500 base pairs (bp) long and encodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This highly tuned system, discovered in mammals, plays a notable role in the hypoxia response of fish. Analysis of icefish mRNA revealed that the functional domains of Hif-1-alpha are highly conserved, indicating continued selective pressure exerted by hypoxia (Rix et al, 2017). These and other hypoxia response gene relationships have been characterized in detail in the hypoxic fish database, HRGFish, which provides a variety of prediction tools and validation methods to further evaluate the conservation of hypoxia genes in diverse fish species (Rashid et al, 2017).…”
Section: Fish Cell Culturementioning
confidence: 99%
“…This highly tuned system, discovered in mammals, plays a notable role in the hypoxia response of fish. Analysis of icefish mRNA revealed that the functional domains of Hif-1-alpha are highly conserved, indicating continued selective pressure exerted by hypoxia (Rix et al, 2017). These and other hypoxia response gene relationships have been characterized in detail in the hypoxic fish database, HRGFish, which provides a variety of prediction tools and validation methods to further evaluate the conservation of hypoxia genes in diverse fish species (Rashid et al, 2017).…”
Section: Fish Cell Culturementioning
confidence: 99%
“…This highly tuned system, while discovered in mammals, plays a notable role in the hypoxia response of fish. Analysis of icefish mRNA revealed that the functional domains of Hif1-alpha are highly conserved indicating the continued selective pressure exerted by hypoxia (Rix, Grove, and O'Brien 2017). These and other hypoxia response gene relationships and predictions have been characterized in greater detail in the hypoxic fish database, HRGFish, available online, which provides a variety of prediction tools and validation methods to further evaluate the conservation of hypoxia genes in diverse fish species (Rashid et al 2017) In the absence of research on the oxygen requirements of fish cell culture in bioreactor systems, the authors speculate that the multitude of genetic adaptations of fish to staggering levels of hypoxia suggest that fish tissues may be uniquely suited to the oxygen-limited environments found in tissue culture and bioreactor conditions.…”
Section: Of Fishmentioning
confidence: 99%